2020
DOI: 10.1159/000510920
|View full text |Cite
|
Sign up to set email alerts
|

Cronkhite-Canada Syndrome Successfully Treated by Corticosteroids before Presenting Typical Ectodermal Symptoms

Abstract: Cronkhite-Canada syndrome (CCS) is a rare disease characterized by diffuse gastrointestinal polyposis with chronic diarrhea and ectodermal change, but its etiology is unknown. We present a case at the age of 26 years complaining of epigastralgia and weight loss. Endoscopic examination revealed extensive diffuse polypoid lesions of the stomach and the terminal ileum, all of which showed hyperplastic polyps pathologically. There were no polypoid lesions in his colon. He has no family history of diffuse gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“… 6 A study reported that clinical manifestations of CCS can be divided into five types based on initial symptoms: i) diarrhoea; ii) taste abnormalities; iii) dry mouth; iv) hair loss and nail atrophy; and v) loss of appetite, malaise, nail atrophy, hair loss, and dysgeusia in the absence of diarrhoea. 4 The case in the study reported few consistent symptoms such as diarrhoea and ectodermal changes. Gastrointestinal polyposis is closely related to the malabsorption which induced these ectodermal changes as well as diarrhoea.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“… 6 A study reported that clinical manifestations of CCS can be divided into five types based on initial symptoms: i) diarrhoea; ii) taste abnormalities; iii) dry mouth; iv) hair loss and nail atrophy; and v) loss of appetite, malaise, nail atrophy, hair loss, and dysgeusia in the absence of diarrhoea. 4 The case in the study reported few consistent symptoms such as diarrhoea and ectodermal changes. Gastrointestinal polyposis is closely related to the malabsorption which induced these ectodermal changes as well as diarrhoea.…”
Section: Discussionmentioning
confidence: 77%
“… 11 A study revealed that appropriate medical therapy can alter the natural history of CCS. 4 Oral corticosteroid therapy (30-49 mg/day) appeared to be effective for active CCS. Its benefits, including clinical improvement and polyp regression, are usually apparent within 12 months.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations